Increase in distal esophageal wall thickness with time in adult patients with eosinophilic esophagitis - Stephanie Wong; Romina Safaeian; Joshua Zobel; Richard H Holloway; Andrew Ruszkiewicz; Nam Q Nguyen (JGH Open, 2023)
Abstract Background and Aim Eosinophilic esophagitis (EoE) is a chronic disease which may progress to a fibro‐stenotic phenotype due to esophageal sub‐epithelial fibrosis. Esophageal wall thickening in patients with EoE has been demonstrated in a few studies using endoscopic ultrasound (EUS). The aim of this study was to longitudinally assess the endoscopic appearance, wall thickness, histology, and dysphagia score of EoE patients. Methods Patients with EoE were recruited and studied between February 2012 and April 2021. Patients were evaluated on two separate occasions at least 12 months apart with endoscopy, EUS, and esophageal mucosal biopsies. The dysphagia score and epidemiology data were also assessed. Results A total of 16 EoE patients were included with a mean follow‐up duration of 2.2 ± 1.2 years. In 14/16 (88%) patients, the total wall thickness of the distal esophagus significantly increased (P = 0.0012) as a result of thickening of the muscularis propria (P = 0.0218). However, only 1/14 (7%) patient had an increase in the dysphagia score, while 8/14 (57%) and 5/14 (36%) had a stable and reduced dysphagia score, respectively. No differences were found in the total thickness of other esophageal regions, dysphagia score, endoscopic appearance, and eosinophil count over time. Conclusion Distal esophageal wall thickness increases with time in EoE patients, independent of the dysphagia score and eosinophil count.